2020
DOI: 10.1155/2020/9435242
|View full text |Cite
|
Sign up to set email alerts
|

Primary Cutaneous CD30+ Anaplastic Large T Cell Lymphoma in a Patient Treated with Cyclosporine for Actinic Reticuloid

Abstract: Actinic reticuloid (AR)—a subtype of chronic actinic dermatitis—clinically and histopathologically shows lymphoma-like features. We report a male patient initially diagnosed with erythrodermic cutaneous T cell lymphoma (CTCL) who developed severe broadband photosensitivity. Clinical evaluation, histopathology, and phototesting were consistent with AR. The patient was treated with cyclosporine 150–300 mg/d. Under this therapy, he developed several times primary cutaneous anaplastic large cell lymphomas (C-ALCL)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Some immunosuppressive drugs we used as MAR-directed therapy have been linked with CTCL exacerbation, including ciclosporin and dupilumab. [34][35][36][37][38] They are theorized to lower or ameliorate any remaining level of antitumour host response, and are thus contraindicated in patients with CTCL. However, we recently published a case report detailing the successful use of dupilumab as a MAR-directed therapy, with special consideration of several conflicting reports of dupilumab when used as a CTCL-directed therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some immunosuppressive drugs we used as MAR-directed therapy have been linked with CTCL exacerbation, including ciclosporin and dupilumab. [34][35][36][37][38] They are theorized to lower or ameliorate any remaining level of antitumour host response, and are thus contraindicated in patients with CTCL. However, we recently published a case report detailing the successful use of dupilumab as a MAR-directed therapy, with special consideration of several conflicting reports of dupilumab when used as a CTCL-directed therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Some immunosuppressive drugs we used as MAR‐directed therapy have been linked with CTCL exacerbation, including ciclosporin and dupilumab 34–38 . They are theorized to lower or ameliorate any remaining level of antitumour host response, and are thus contraindicated in patients with CTCL.…”
Section: Discussionmentioning
confidence: 99%
“…Primary treatment of HIV‐related photosensitive dermatosis is HAART and sun avoidance; secondary supportive treatment is required according to initial lesions and the progression. Cyclosporin, thalidomide, and mycophenolate mofetil are helpful 33–36 …”
Section: Discussionmentioning
confidence: 99%
“…Chronic actinic dermatitis (CAD) is an immune-mediated photoallergic skin disease accompanied with skin barrier dysfunction, which can be converted into cutaneous lymphoma in severe cases. 1 This disease seriously affects both physical and mental health, and reduces the quality of life of patients. 2 Recent reports have shown that with the increase of climate change and environmental pollution, the incidence of CAD has shown a significant upward trend.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic actinic dermatitis (CAD) is an immune‐mediated photoallergic skin disease accompanied with skin barrier dysfunction, which can be converted into cutaneous lymphoma in severe cases 1 . This disease seriously affects both physical and mental health, and reduces the quality of life of patients 2 .…”
Section: Introductionmentioning
confidence: 99%